PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PT TRI CIPTA SUKSES MANDIRI DI KOTA BATAM - Yap, David; Yuliadi, Yuliadi (SCIENTIA JOURNAL, 2019)
The purpose of this study was to analyze the effect of revenues and receivables turnover on the profitability of Tri Cipta Sukses Mandiri. The search will be performed using multiple regression analysis. The results of the details of this study indicate that the turnover has a significant effect on profitability. can be proved by the probability of 0.000 <0.05, concluded that hypothesis 1 of this study was accepted. While the results of the second hypothesis indicated by the turnover of the receivables do not have a significant effect on the profitability, this can be proved by the probability of Sig 0,231> 0,05, it is concluded that the second hypothesis of this study was rejected. And for the 3rd hypothesis in this study indicated by the turnover and the turnover of the receivables has an influence on the profitability, by looking at the probability of 0.000 <0.05, it is concluded that the third hypothesis this study is accepted. Looking at the R2 test, we can conclude that the probability variable can be explained by 67.3% of turnover in cash and the claim and that the remaining 32.7% can be explained by other variables, outside of this research.